Similarities and Discrepancies in English and Uzbek Children’s Prose (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Background. This article deals with the interchangeability of children's and teenagers' literature, their names, the direction of literary works, the nature, and the diversity of the world of protagonists that clearly shows the difference between English and Uzbek children's literature.Methods. Transformational, comparative-typological, comparative-historical, functional-interpretative, linguopoetic, classification, psychoanalytic, and biographical analysis methods were used in the article. It is noted that such literary works vividly reflect the realistic image of children, their mental experiences, the world of childhood and youth, full of emotions, their adventures, as well as, their "unhappy childhood".Moreover, the genre of the novel "Oliver Twist" is part of the bildungsroman series by Charles Dickens. "Oliver Twist" is about orphan hood, loneliness, and a child who is tormented by cruel people who make use of the labor of a young boy; the complex psychology and inner world of a young teenage boy; his years of unhappiness full of conflicts were also delineated in the novel.Thus, the vivid expression of childhood is depicted with high artistic pathos in the English literature of the XIX th century. The most significant point is that the world of childhood was discovered in literature, the extraordinary position of childhood and adolescence was clear for every person, and the writers who lived during this period paid great attention to the spiritual world of teenagers.Results. Various characters were created in children's literature with the development of realistic principles in English literature, and it served as the basis for the emergence of literary psychologism. Writers managed to uncover the secrets of the stage of the formation of the human personality, the source of perfection, by looking into the image of children in literature, looking into their inner world and discovering their complex characteristics. As a result, the skill of the best writers is determined by how high artistic pathos they express of childhood and the talent to deeply explore the psychology of teenagers. In this sense, based on legends and narratives, animalistic stories and literary tales appeared. In particular, in children's literature, it can be observed that famous authors created artistic works in various genres. The "absurd fairy tales" and "nonsense fairy tales" created by poets and writers such as R. Kipling, H. Lofting, B. Potter, K. Graham, really constitute a rich treasure of not only English children's literature but also world children's prose.Conclusion. Modern children's literature is rapidly growing day by day. According to investigations, researchers have pointed out that, unlike the children of the past, modern children have the opportunity to see a lot of information that shows about natural disasters, wars of world countries, vandalism and destruction on television and the Internet. In addition, it is natural for them to watch pornographic shows inappropriate for their youth through social networks. But children's writers are still limiting children's literature. The expression of the hero's psychology, the dynamics of their personality formation and the compositional-artistic features are deemed to be important to study in English and Uzbek children's literature as comparative literary criticism.